1997
DOI: 10.1046/j.1365-2729.1997.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Automatic assessment of elementary Standard ML programs using Ceilidh

Abstract: Ceilidh is an interactive environment which supports computer programming course organisation, practical work and assessment. This paper describes its use to support a first level programming course for the functional language Standard ML. Automated program assessment systems are surveyed and the general Ceilidh approach to automatic assessment is discussed. Extensions to Ceilidh to assess Standard ML programs are considered and an evaluation is made of the effects of its use on student learning. The main conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…It is inconceivable to use a computer to assess large, important, predominantly creative projects such as a final year creative writing essay or a final year arts project. Computers are, however, used to assess some large creations, such as computer programs ( Foubister, Michaelson & Tomes, 1997;Foxley, Higgins, & Tsinitsifas, 1998), although a computer program clearly exists in a tightly defined environment and has a relatively small artistic component.…”
Section: Virtuementioning
confidence: 99%
“…It is inconceivable to use a computer to assess large, important, predominantly creative projects such as a final year creative writing essay or a final year arts project. Computers are, however, used to assess some large creations, such as computer programs ( Foubister, Michaelson & Tomes, 1997;Foxley, Higgins, & Tsinitsifas, 1998), although a computer program clearly exists in a tightly defined environment and has a relatively small artistic component.…”
Section: Virtuementioning
confidence: 99%
“…Higgins and Bligh [7] have analyzed whether computer based assessment (CBA) meets pedagogic criteria for measuring the quality of assessment suggested by Brown et al (1996). Table 1, which is taken directly from [7] shows the analysis. Based on the analysis, they concluded that CBA meets 7 out of 10 criteria, therefore CBA can be said to have concrete pedagogic benefits.…”
Section: Automatic Marking Criteriamentioning
confidence: 99%
“…From the modeling aspect, [9] try to formalize automatic marking system in order to have a depth Table 1: Application of assessment criteria to CBA [7] Criterion Application to CBA Valid Will measure specified coursework aspects assuming good initial assessment design Reliable…”
Section: Automatic Marking Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Program graders are not new [2], however one of the things that distinguishes TorqueMOODa, is its integration into an existing learning system. A predecessor system [5] had a lesser scope and completely different implementation.…”
Section: The Program Gradermentioning
confidence: 99%